Digital identity management system for mine hydraulic props based on dual-mode wireless communication - ZHANG Can; LU Liqun; GENG Wenpeng; FU Shanshan; XIE Xinyu (Gong-kuang zidonghua, 2025)
The traditional management and maintenance mode of single hydraulic supports used in mining is inefficient, difficult to trace, and has low safety. However, in the underground coal mine environment, RFID-based management systems for single hydraulic supports are easily affected by metal interference, which degrades identification performance, and their data communication heavily relies on a single network, making it difficult to ensure stable and real-time communication. To address these issues, a digital identity management system for mining single hydraulic supports based on dual-mode wireless communication and RFID was designed, using PCB ultra-high-frequency anti-metal tags to reduce metal environment interference on RFID. By scanning the RFID tags on hydraulic supports with a handheld reader, the basic information and status (normal, fault, scrap, etc.) of the hydraulic supports could be read. The handheld terminal app provided a one-click upload function to wirelessly send the hydraulic support status data to server-side management software, achieving full lifecycle monitoring and management of the hydraulic supports. To adapt to the complex underground wireless environment, a dual-mode wireless communication method was proposed, intelligently switching between public WiFi and AP hotspots, effectively solving the problem of insufficient network coverage underground and ensuring reliable data transmission. A dynamic data value evaluation model based on information entropy theory was introduced to implement a data-value-based dynamic hierarchical transmission strategy. Test results showed that the PCB ultra-high-frequency anti-metal tag had an effective identification distance of 2.2 meters under unobstructed conditions, with identification stability reaching 98%. Under WiFi mode, the system’s effective data transmission distance was 5.2 meters, with a transmission success rate above 90%.